(untitled) (Research, Society and Development, 2021)
Objective: to investigate the scientific evidence on care in the use of aromatherapy in labor. Methodology: this is an integrative review, it was carried out between December and January 2021, in the database National Library of Medicine National Institutes of Health, and in the virtual libraries Scientific Electronic Library Online, and Virtual Health Library. Results and Discussion: They remained in study 9, as they were considered consistent with the proposal of the review. The issue of safety in the use of these essential oils seems to be easy to approach, however, the discussion regarding their toxicity is much more complex. It should be considered that essential oils exert their effects not only physical, but also effects with direct action on the brain, bringing consequences that are often irreversible, pure oils often have high toxicity, so much so that, within the recommendations for use, they are found small dosages. Conclusion: the adoption of aromatherapy and other PIC associated with the rescue of its scientific bases, has benefits in labor validated by several scientific evidences.